2019
DOI: 10.7717/peerj.8203
|View full text |Cite
|
Sign up to set email alerts
|

Feeding intensity of insect herbivores is associated more closely with key metabolite profiles than phylogenetic relatedness of their potential hosts

Abstract: Determinants of the host ranges of insect herbivores are important from an evolutionary perspective and also have implications for applications such as biological control. Although insect herbivore host ranges typically are phylogenetically constrained, herbivore preference and performance ultimately are determined by plant traits, including plant secondary metabolites. Where such traits are phylogenetically labile, insect hervivore host ranges are expected to be phylogenetically disjunct, reflecting phenotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…Strong positive correlation of butterfly assemblages to plant secondary metabolite composition has been found in a number of host plant genera-moth family interaction networks (Endara et al, 2017) and in other insect herbivore communities (Becerra, 1997;Endara et al, 2018). Especially in specialist insect clades, secondary metabolite similarity was found to be a better predictor for feeding intensity than phylogenetic relatedness of host plants (Becerra, 1997;Pearse & Hipp, 2009;Rapo et al, 2019;Rasmann & Agrawal, 2011).…”
Section: An Overview Of the Total Interaction Communitymentioning
confidence: 93%
See 1 more Smart Citation
“…Strong positive correlation of butterfly assemblages to plant secondary metabolite composition has been found in a number of host plant genera-moth family interaction networks (Endara et al, 2017) and in other insect herbivore communities (Becerra, 1997;Endara et al, 2018). Especially in specialist insect clades, secondary metabolite similarity was found to be a better predictor for feeding intensity than phylogenetic relatedness of host plants (Becerra, 1997;Pearse & Hipp, 2009;Rapo et al, 2019;Rasmann & Agrawal, 2011).…”
Section: An Overview Of the Total Interaction Communitymentioning
confidence: 93%
“…Ecological theory suggests that similarity of host functional traits might better explain congruence between butterflies and their host plants than phylogenetic relationships alone. Such host plant similarity may be in the form of ecological niches, structural defenses, biotic defenses, seasonal palatability, nutritional composition, or secondary metabolite composition (Becerra, 1997;Endara et al, 2017;Murphy & Feeny, 2006;Pearse & Hipp, 2009;Rapo et al, 2019). Indeed, there is growing evidence for the importance of chemical defenses in shaping herbivore assemblages and driving coevolutionary interactions of butterflies and their host plants (Ferrer-Paris et al, 2013;Fordyce, 2010;Janz et al, 2001;Wahlberg, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This shared morphological similarity is to be expected, as all three of the latter taxa are members of the Scheerianae clade, while O. humifusa is phylogenetically separate and in the Humifusa clade (Majure et al, 2012). An alternative hypothesis to the selective behaviour of this cochineal could be that secondary compounds produced by the host plants are what cochineal insects use to accept their host, and will dictate whether or not a host is suitable (Rapo et al, 2019). Secondary metabolites may offer a useful area of investigation to determine what makes a host suitable for this valuable cochineal.…”
Section: Suitability Of Opuntia Taxa To the 'Stricta' Lineagementioning
confidence: 99%
“…Alternatively, secondary metabolites similarity among potential host plants may explain host suitability of a specialised insect herbivore, sometimes more so than the phylogenetic relatedness of these particular plant species (Kergoat et al, 2005;Murphy & Feeny, 2006;Rapo et al, 2019). Weber et al (2019) have shown a population of wild strawberries to differ in their acceptability ('antixenosis' = beetle preference = acceptability) and suitability ('antibiosis' = beetle survival and performance = suitability) of the strawberry leaf beetle (Garelucella tennela L.).…”
Section: Introductionmentioning
confidence: 99%
“…Insect herbivores may exert selection that promotes novel defence strategies in plants and these events often coincide with radiation of herbivore species that have counteradaptations to these novel defences (Edger et al 2015). Even though the relationship between plant phylogenetic distance and overlap in herbivore communities is variable across plant clades, co-evolutionary processes often result in non-random structuring of plantassociated antagonist communities (Bergamini et al 2017, Rapo et al 2019 . CC-BY 4.0 International license perpetuity.…”
Section: Introductionmentioning
confidence: 99%